OVERWEIGHT AND OBESITY RISK ASSESSMENT - TWO METHODS, DIFFERENT RESULTS - Pop, Cristiana Lucretia (Physical Education of Students, 2016)
Purpose: the purpose of this study was to verify if there is any significant difference between body fat assessment by calculating body mass index and by using bioelectrical impedance analysis. Materials: subsequently we determined the ratio between body fat and muscular mass percentage in a sample of 156 university girl students. Results: BMI and muscle mass percentage seem to have similar variance and trends, while body fat exceeded in numbers and percents the highest levels of BMI. While by calculating BMI the found number of overweight and obese subjects was 23 from the total of 156, (14 %); by measuring body fat percentage that number increased to 67 (43%) of girl students in the sample. The t test showed significant difference between BMI values and the body fat percentage for the study sample: t (155) = 2.37, p-0.01. Conclusions: this study supports the idea that BMI results may be insufficient for correct assessment of overweight and obesity risk. Body composition adds useful information about health and fitness. A few concluding recommendations, regarding beneficial effects of exercise, have been made aiming to provide students of all body parameters with meaningful, relevant and positive physical education and health knowledge.